Pengaruh Ekstrak Etanol Tangkai Begonia multangula Blume Terhadap Biofilm Bakteri Aggregatibacter actinomycetemcomitans - Haidy Lailatun Nabila (Fakultas Farmasi Universitas Setia Budi, 2022)
Aggressive periodontitis is a type of peridontitis with rapid disease progression and destruction. One of the causes of aggressive periodontitis is the presence of Aggregatibacter actinomycetemcomitans biofilm. Prevention of biofilm formation is one way to prevent aggressive periodontitis. The stalk of B. multangula Blume has antibacterial activity and has the potential to be used as an antibiofilm. This research aimed to determined antibiofilm activity of etanol extract of the stalk B. multangula Blume against A. actinomycetemcomitans.. This research used 5 concentration of extract (6,25%, 12,5%, 25%, 50% and 100%), Negative Control (Aquades sterile) and Positive Control (CHX 0,2%). Inhibition biofilm test using microtitter plate biofilm assay with crystal violet staining at anaerobic incubation for 24 hours and using microplate reader at 620 nm. One way ANOVA and post hoc LSD were used to analyze the differences in antibiofilm activity. The result showed inhibition biofilm activity of A. actinomycetemcomitans by the extract increased as increasing of the concentration. The highest biofilm inhibition was at 100% (74,92%) of the extract concentration and Minimum Biofilm Inhibition Concentration 50 (MBIC50) against A. actinomycetemcomitans was found at 25% (54,42%) of the extract concentration. There were significant difference (p≤0,05) between treatment group of etanol extract (concentration 6,25%, 12,5%, 25%, 50%, and 100%) with negative control and there were no significant difference (p≥0,05) in the positive control with 50% and 100% of the extract concentration. This study concluded that there was an antibacterial activity etanol extract of the stalk B. multangula Blume against inhibition biofilm of A. actinomycetemcomitans.